Fuel cell/supercapacitor passive configuration sizing approach for vehicular applications. (9th October 2020) - Dépature, Clément; Macías, Alvaro; Jácome, Andres; Boulon, Loïc; Solano, Javier; Trovão, João P.
Abstract: Active configuration i.e., source coupling via a power converter, is the most common configuration for fuel cell/supercapacitor (FC/SC) vehicles. Passive connection of the FC with the SCs without any converters is an original and less expensive solution to distribute the power among the sources. This passive configuration does not require an energy management strategy. In fact, the power distribution only depends on the FC and SC impedance characteristics. Conventional methods to size the SC follow two criteria: storage capacity and maximum voltage. In this paper, a third criterion is added which is the FC operating current dynamics. This novel sizing methodology reduces the FC degradation and improves the global system efficiency. Experimental results provide validation to the proposed sizing approach. The SCs boost the FC to meet the requirements of the load with a guarantee of system stability reaching higher global performances and less stress to the FC. Highlights: Low-cost passive configuration between fuel cell and supercapacitor is employed. A frequency-based sizing methodology is proposed for the fuel cell system. Higher global performance and less stress to the fuel cell system are achieved.